Kinetics of relapse after pegylated interferon and ribavirin therapy for chronic hepatitis C. Issue 7 (22nd May 2013) - Brochot, Etienne; Riachi, Ghassan; Plantier, Jean‐Christophe; Guillemard, Catherine; Vabret, Astrid; Mathurin, Philippe; Nguyen‐Khac, Eric; Duverlie, Gilles; ,
Abstract To optimize standard treatment of chronic hepatitis C in responder patients who have achieved undetectable viral load, a prospective study was conducted to determine the factors and kinetics of virologic relapse. Responder patients were monitored 2, 4, 8, 12, 16, and 24 weeks after the end of treatment with pegylated interferon and ribavirin. Forty‐seven of the 154 patients (30.5%) relapsed. Relapse was significantly associated with absence of rapid virologic response (RVR), retreatment, higher baseline viral load, older age, and lower weight‐based dose of pegylated interferon. Relapse was more frequent in patients failing to achieve a RVR after receiving pegylated interferon alpha 2a < 2.5 µg/week or alpha 2b < 1.5 µg/week (P = 0.002). Among patients infected with hepatitis C virus (HCV) genotype 1 with non‐CC IL‐28B polymorphism (rs12979860), viral decay during treatment was lower in relapsers (P = 0.003 at week 4). Relapse was detected at weeks 2, 4, 8, and 12 after the end of treatment for 5, 8, 10, and 6 patients infected with HCV genotype 1, respectively. Positive predictive values for sustained virologic response were 70.9%, 80.2%, 91.9%, and 98.8% at weeks 2, 4, 8, and 12, respectively. Only one patient relapsed beyond 24 weeks. Closer follow‐up and treatment adaptation in patients failing to achieve RVR may decrease the relapse rate in slower responders and heavier patients. Monitoring viral load as early as 1 month after the end of treatment could be useful to assess virologic response. J. Med. Virol. 85:1191–1198, 2013. © 2013 Wiley Periodicals, Inc.